Implementasi Metode Demonstrasi Untuk Meningkatkan Keaktifan Siswa Pada Pelajaran Fiqih Kelas XI MAN 1 Kota Bogor - Muhammad Ilham Rabbani; Syarifah Gustiawati; Hambari (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2025)
The demonstration method is a learning method that uses demonstrations to clarify a concept or to show the whole class about a process or instructions for doing something. Implementation of the Demonstration Method to increase student activity, so that they can interact more easily with teachers or classmates and can make it easier to understand the material presented by the teacher. This study aims to determine the implementation of the demonstration method in Fiqh learning at MAN 1 Bogor City, and its impact on student activity. The demonstration method was chosen because it can increase student interaction with teachers and friends, and make it easier to understand the material. The study used a qualitative approach through observation, interviews, documentation, and questionnaires, with data analysis in the form of reduction, presentation, and drawing conclusions. The results of the paired sample t-test showed an increase in student activity by 29.27% ​​after the implementation of the demonstration method. The supporting factors for the success of this method are student enthusiasm and the relevance of the material, while the inhibiting factors include limited time and facilities.